The knowledge about cervical cancer among female students of Lublin universities - Żminda, Agata; Bakalczuk, Grzegorz; Putowski, Maciej; Padała, Olga; Piróg, Marta; Wdowiak, Artur (Journal of Education, Health and Sport, 2017)
Introduction and the aim of the study Cervical cancer has been a serious epidemiological problem in Poland for many years. The simplest and the most cost-effective way to detect this cancer is to perform a regular cytological examination. The disease is most often diagnosed at an advanced stage, which is due to the low prevalence of women for prophylaxis. The aim of the study was to analyze the level of knowledge of female students about cervical cancer, its treatment and prophylaxis. Material and methodology The study included 250 randomly selected female students from Lublin universities aged 19 to 44 years. The author’s questionnaire was used. The obtained results were analyzed statistically. The significance level was assumed as p<0.05. Data base and statistical studies were performed on STATISTICA 13.0 software (StatSoft, Poland). Results Statistical analysis showed that the respondents studying at the Medical University had significantly higher level of knowledge about cytological examination than those who studied at other universities (H=35.85, p<0.0001). The respondents most frequently performed self-initiated cytology (36.00%, n=90), while 24.00% (n=60) reported that at the doctor’s initiative, 0.80% (n=2) on the initiative of midwife and 39.20% (n = 98) did not examine. As a result of the studies, it was shown that respondents with good or very good financial status were more likely to have a higher level of knowledge about cervical cancer (19.89%) than low status (7.59%) (Chi2=6.30 p=0.04). Statistical analysis showed that the respondents aged 22 and over were more likely to have heard about the Prevention and Early Detection Program for Cervical Cancer, organized by the National Health Fund (NFZ) than the younger ones (33.33%) (Chi2=11.91, p=0.003). Conclusions The level of knowledge of female students in Lublin about cervical cancer seems to be insufficient. There is a need to educate women in the prevention and diagnosis of this cancer. The most commonly pointed source of knowledge about cervical cancer was the Internet. This makes it possible to improve young women’s knowledge by conducting large-scale information campaigns on social networking sites or on websites concerning health. Doctors should pay particular attention to the educational aspect of patient care.